SCHOOL LEVEL MENSTRUAL HYGIENE MANAGEMENT IN OROMIA REGION OF ETHIOPIA - Kaba, Mirgissa; Adugna, Zelalem (Ethiopian Journal of Reproductive Health, 2020)
Abstract Background: Menstruation is a biological occurrence for women of reproductive age. Its management and men’s role however is determined by socio-cultural factors. Yet, there is limited evidence on support and guidance girls obtain from boys on menstrual hygiene and management. This study aims to identify school based menstrual hygiene and management interventions and the role of boys in Oromia region, Ethiopia. Method: The study was carried out in 2017-18 academic year in eight Oromia Development Association supported public schools where sport for life interventions were running. Schoolboys and girls aged 12-15, parents and school teachers participated in the study. Focus Group Discussion (FGDs) with boys and girls and key informant interviews (KII) with parents were completed. Data so collected were transcribed and translated into English and themes were developed following the objective of the study. Interpretation and presentation of the findings were made substantiated with shared opinions directly quoted. Findings: The study shows that after two years of school based intervention boys in the study schools and parents recognized menstruation as a natural biological occurrence and a blessing rather than a curse. Common arguments by all participants alike show that ‘We learnt that menstruation is a mark of healthy growth of girls. It should be the absence of it that should be the source of concern’. With dedicated room, sanitary napkin and positive recognition from boys and schoolteachers, management of menstrual hygiene became easier. Boys not only stopped teasing girls but also started contributing money to purchase sanitary napkins. Liaising such school level intervention with parents extended support to girls to home. Conclusion: Although further study with mixed method may help to document level of changes, school level awareness raising on Sexual Reproductive Health and mobilization of resources for management of menstrual hygiene could improve girl’s academic performance. Key terms: Menstrual hygiene, adolescents, Sexual Reproductive Health, Oromia, Ethiopia